Success in Everyday Life - Paszenda, Iwona (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2020)
The aim of this article is the analysis of influences of the cultural processes on the way of thinking about success in everyday life. The foundation for the reflections is constituted by the results of survey research reflecting transformation which took place within this area from the end of the 1980s up to the post-modern period. The research results prove that the category of success is not a stable social construct and the society members assign contradictory values to this notion. Those disadvantageous lead to number of tensions. The article presents alternative ways of human’s reaction to these tensions and consequences such approach entails. The conclusions drawn with regards to education provide a summary for the overall reflections.
Keywords: Brameld, Theodore